STUDI OZONISASI SENYAWA ORGANIK AIR LINDI TEMPAT PEMROSESAN AKHIR SARIMUKTI - Arya Rezagama (TEKNIK, 2013)
Existing treatment leachate from Sarimukti Landfill doesn’t meet the quality standards of waste water.Preliminary treatment is necessary to break down persistent leachate compounds. Ozone can act directly orindirectly with organic material (Glaze 1986). Column batch reactor system use one liter volume. Ozone ispumped into the leachate in the form of fine bubbles. Variations include Ozone Pumping Flow, Ratio ofhigh/diameter (t/d), and pH. Kinetic Reaction of oxygen dissolution in the average leachate is zero order.Increased pumping air discharge and increased pH makes ozone transfer process better. Best value occurs at pH11, where the value of the reaction rate constant ozone 1.48. The average percentage of organic materialallowance 31% COD and 26% TOC. The decline TOC and COD have a tendency to be influenced by the pHoptimum 8-9. At alkaline pH makes carbonate (CO3) formed the greater, that make ozone compounds killquickly. FTIR results showed the intensity of hydroxyl groups increased after ozone oxidation where thesubstitution of functional groups of organic matter associated with electrophilic addition reaction of oxygenatoms. Existence Fulfic acid also increased the effect compounds and Humic Acid, Humad large has been cut byradicals.